A Systematic Review on the Impact of Vaccination for Respiratory Disease on Antibody Titer Responses, Health, and Performance in Beef and Dairy Cattle - Hudson R. McAllister; Bradly I. Ramirez; Molly E. Crews; Laura M. Rey; Alexis C. Thompson; Sarah F. Capik; Matthew A. Scott (Veterinary Sciences)
Bovine respiratory disease (BRD) is a multifactorial disease complex commonly affecting beef and dairy operations. Vaccination against major BRD-related pathogens is routinely performed for disease prevention; however, uniform reporting of health and performance outcomes is infrequent. Our objective was to evaluate the effect of commercially available BRD-pathogen vaccination on titer response with respect to health or performance in beef and dairy cattle. This study was conducted under Prisma 2020 guidelines for systematic reviews and PRESS guidelines utilizing five databases. Criteria for study inclusion were as follows: research conducted in the USA or Canada, between 1982 and 10 October 2022, on beef or dairy cattle, using a commercially available vaccine labeled for a respiratory pathogen of interest, which evaluated antibody titers alongside either performance or morbidity. A total of 3020 records underwent title and abstract evaluation. Full-text analysis was conducted on 466 reports; 101 studies were included in the final review. Approximately 74% of included studies were beef cattle-based versus 26% dairy cattle-based. This review aimed to assess how vaccination titer responses affect beef and dairy cattle health and performance, but varying study methods made comparisons difficult, highlighting the need for consistent reporting.